2009
DOI: 10.1007/s11244-008-9167-z
|View full text |Cite
|
Sign up to set email alerts
|

DRIFT, XPS and XAS Investigation of Au–Ni/Al2O3 Synergetic Catalyst for Allylbenzene Isomerization

Abstract: Au/Al 2 O 3 and Ni/Al 2 O 3 prepared by deposition-precipitation and impregnation methods, respectively, and Au-Ni/Al 2 O 3 prepared by impregnation of the Au/ Al 2 O 3 system with nickel have been studied by physicochemical methods. The catalysts were tested in allylbenzene isomerization at 443 K. The isomerization on Au/Al 2 O 3 proceeds with a rather low rate, while monometallic Ni/Al 2 O 3 is inactive. Unlike monometallic catalysts, Au-Ni/Al 2 O 3 demonstrates a strong synergetic effect: the isomerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 16 publications
1
19
1
Order By: Relevance
“…The addition of tin to the Pt/SiO 2 catalyst produced a remarkable positive shift in both the product distribution and TOF in the liquid-phase hydrogenation of unsaturated aldehyde to corresponding alcohols [43,44]. The simultaneous increase in both activity and selectivity indicates the formation of a new type of mixed (M x+ )/(Pt) 0 clusters, different in nature when Our investigations of model Au, Ni/Au, and Ni catalysts by XPS, DRIFT, and XAS techniques showed that nickel in both Ni/Au and Ni catalysts exists as NiO, gold in the Au catalyst exists as Au 0 nanoclusters, whereas the Au 0 nanoclusters co-exist with Au 3+ cations in the NiO/Au samples [7]. Then, the first probable explanation (I) of synergistic activity between NiO and Au in ethyne hydrogenation (Table 1) could be due to the electron transfer from the electron-rich Au 0 particles to the electron-deficient NiO that give new Au δ+ catalytic sites.…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…The addition of tin to the Pt/SiO 2 catalyst produced a remarkable positive shift in both the product distribution and TOF in the liquid-phase hydrogenation of unsaturated aldehyde to corresponding alcohols [43,44]. The simultaneous increase in both activity and selectivity indicates the formation of a new type of mixed (M x+ )/(Pt) 0 clusters, different in nature when Our investigations of model Au, Ni/Au, and Ni catalysts by XPS, DRIFT, and XAS techniques showed that nickel in both Ni/Au and Ni catalysts exists as NiO, gold in the Au catalyst exists as Au 0 nanoclusters, whereas the Au 0 nanoclusters co-exist with Au 3+ cations in the NiO/Au samples [7]. Then, the first probable explanation (I) of synergistic activity between NiO and Au in ethyne hydrogenation (Table 1) could be due to the electron transfer from the electron-rich Au 0 particles to the electron-deficient NiO that give new Au δ+ catalytic sites.…”
Section: Resultsmentioning
confidence: 75%
“…An increase in the surface positive charge on Au due to electron transfer [7] improves the electron acceptor properties of gold and thereby should lead to stronger adsorption of ethyne or ethene on Au δ+ than on Au 0 and, therefore, increase the probability of the chemical reaction. Table 2 shows that positive charge on the flat as well as on the Au 12 + (2D) and Au 12 + (3D) cluster leads to an increase in the heat of adsorption of ethene in π-complex up to 132 and 147 kJ/mol, respectively.…”
Section: The Nature Of Au Activation In Nio/au Clustersmentioning
confidence: 99%
See 3 more Smart Citations